Advanced Hydrogels With Nanoparticle Inclusion for Cartilage Tissue Engineering - Ao, Yunong; Zhang, En; Liu, Yangxi; Yang, Liu; Li, Jun; Wang, Fuyou (Frontiers in Bioengineering and Biotechnology, 2022)
Cartilage dysfunctions caused by congenital disease, trauma and osteoarthritis are still a serious threat to joint activity and quality of life, potentially leading to disability. The relatively well-established tissue engineering technology based on hydrogel is a promising strategy for cartilage defect repairing. However, several unmet challenges remain to be resolved before its wide application and clinical translation, such as weak mechanical property and compromised bioactivity. The development of nanomedicine has brought a new dawn to cartilage tissue engineering, and composite hydrogel containing nanoparticles can substantially mimic natural cartilage components with good histocompatibility, demonstrating unique biological effects. In this review, we summarize the different advanced nanoparticle hydrogels currently adopted in cartilage tissue engineering. In addition, we also discuss the various application scenarios including injection and fabrication strategies of nanocomposite hydrogel in the field of cartilage repair. Finally, the future application prospects and challenges of nanocomposite hydrogel are also highlighted.